Mammalian γ2 AMPK regulates intrinsic heart rate - Yavari, A; Herring, N; Steeples, V; Ghaffari, S; Puliyadi, R; Beglov, Y; Kelly, M; Gehmlich, K; Douglas, G; Ferguson, D; Channon, K; Cornall, R; et al. (Nature Publishing Group, 2017)
AMPK is a conserved serine/threonine kinase whose activity maintains cellular energy homeostasis. Eukaryotic AMPK exists as αβγ complexes, whose regulatory γ subunit confers energy sensor function by binding adenine nucleotides. Humans bearing activating mutations in the γ2 subunit exhibit a phenotype including unexplained slowing of heart rate (bradycardia). Here we show that γ2 AMPK activation downregulates fundamental sinoatrial cell pacemaker mechanisms to lower heart rate, including sarcolemmal hyperpolarization-activated current (If) and ryanodine receptor-derived diastolic local subsarcolemmal Ca2+ releases. In contrast, loss of γ2 AMPK induces a reciprocal phenotype of increased heart rate, and prevents the adaptive intrinsic bradycardia of endurance training. Our results reveal that in mammals, where heart rate is a key determinant of cardiac energy demand, AMPK functions in an organ specific manner to maintain cardiac energy homeostasis and determine cardiac physiological adaptation to exercise, by modulating intrinsic sinoatrial cell behaviour.